Core-shell structure composite conductive material and preparation method and application thereof
Patent Information
- Application Number
- CN202610806671.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-13
AI Technical Summary
常规涂料需大量高密度填料才能达标,进一步加剧沉降问题
本发明提供的核壳结构复合导电材料,使磺化石墨烯均匀嵌入聚苯胺基质形成一体化复合壳层,有效解决了传统导电填料导电性不足、易团聚沉降的关键问题;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, and in particular to a core-shell structured composite conductive material, its preparation method, and its application. Background Technology
[0002] The grounding grid is a core infrastructure for the safe and stable operation of a power system, playing a crucial role in discharging fault currents and lightning currents. Its operational reliability directly determines the safety level of the power grid. However, in complex soil environments containing corrosive ions, acids, or saline-alkali soils, grounding electrodes are subject to long-term electrochemical corrosion, easily leading to problems such as excessive grounding resistance and grounding electrode breakage, posing a risk of equipment "losing ground." With the large-scale popularization of ultra-high voltage transmission projects, the power grid is placing higher standards on the long-term service performance, conductivity stability, and corrosion resistance of the grounding grid. Efficient and reliable corrosion protection technologies have become an urgent requirement for ensuring the safe operation of the power system.
[0003] Traditional grounding grid protection methods have significant shortcomings and are difficult to adapt to the application requirements of modern power grids. Galvanized steel protection corrodes rapidly in harsh soils; in acidic soils, the corrosion rate can reach 6-8 g / dm³ after 1.4 years. 2 • a) The design lifespan of current technologies is far less than 30 years; while copper-clad steel offers excellent corrosion resistance, it is expensive, scarce, and poses a risk of heavy metal pollution to the soil; cathodic protection requires continuous monitoring and maintenance, and regular replacement of sacrificial anodes, with total life-cycle costs reaching 3-5 times the initial investment, making it uneconomical. None of these technologies can simultaneously achieve long-term corrosion protection, high conductivity, low cost, and environmental friendliness. The industry urgently needs new protection solutions to overcome these technological bottlenecks.
[0004] Composite coatings combining conductivity and corrosion resistance have become a research hotspot. Among them, polyaniline shows potential in the field of metal corrosion protection due to its excellent conductivity, chemical stability, and environmental friendliness, inhibiting metal corrosion through a dual mechanism of passivation film formation and barrier effect. However, the intrinsic conductivity of pure polyaniline is limited, which cannot meet the high conductivity requirements of grounding grids discharging kiloampere-level instantaneous currents. Graphene possesses ultra-high intrinsic conductivity (approximately 1×10⁻⁶). 6 Graphene oxide (S / m) is an ideal filler for improving the conductivity of coatings. However, the conjugated structure of graphene oxide is destroyed by oxidation, resulting in decreased conductivity. Reduced graphene oxide has poor dispersibility and is difficult to be compatible with water-based systems, which limits its application.
[0005] Furthermore, the storage stability of conductive coatings is a key bottleneck restricting their engineering applications. The large density differences between high-density metals, graphite fillers, and resin matrices lead to sedimentation and stratification during storage, forming hardened deposits within weeks. This necessitates prolonged stirring before application, reducing efficiency and compromising the uniform conductivity of the coating. According to DL / T 2308-2021 "Technical Conditions for Conductive Anti-corrosion Coatings for Grounding in Power Engineering," the room temperature resistivity of conductive anti-corrosion coatings for grounding in power engineering should not exceed 1.0 Ω·m. In practical engineering applications, grounding grid coatings typically require a volume resistivity ≤ 5 × 10⁻⁶. -3 The required conductivity (Ω·cm) is sufficient to meet the demands of high-current discharge. Conventional coatings require large amounts of high-density fillers to meet these requirements, further exacerbating the sedimentation problem. Therefore, developing novel conductive coatings that combine high conductivity, excellent storage stability, and long-term corrosion resistance has significant engineering value and practical implications. Summary of the Invention
[0006] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one objective of the present invention is to provide a core-shell structured composite conductive material.
[0007] The second objective of this invention is to provide a method for preparing such a core-shell structured composite conductive material.
[0008] The third objective of this invention is to provide a coating.
[0009] The fourth objective of this invention is to provide a coating.
[0010] The fifth objective of this invention is to provide an application for this coating.
[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a core-shell structured composite conductive material, the core-shell structured composite conductive material comprising a core containing nickel particles and graphite particles, and a shell layer covering the surface of the core layer, the shell layer being a composite conductive layer formed by embedding sulfonated graphene nanosheets into a polyaniline matrix.
[0012] In some embodiments of the present invention, the nickel particles have a particle size of 1-5 μm.
[0013] In some preferred embodiments of the present invention, the nickel particles have a particle size of 1-3 μm.
[0014] In some embodiments of the present invention, the particle size of the graphite particles is 1-10 μm.
[0015] In some preferred embodiments of the present invention, the particle size of the graphite particles is 3-8 μm.
[0016] In some embodiments of the present invention, the diameter of the sulfonated graphene nanosheets is 5-15 μm.
[0017] In some embodiments of the present invention, the particle size of the core-shell structured composite conductive material is less than or equal to 200 mesh.
[0018] In some embodiments of the present invention, the core-shell structured composite conductive material comprises the following raw materials: nickel particles, graphite particles, sulfonated graphene nanosheets (SGO), aniline monomer, and dodecylbenzenesulfonic acid (DBSA).
[0019] In some embodiments of the present invention, the mass ratio of the graphite particles to the nickel particles is (3-9):1.
[0020] In some preferred embodiments of the present invention, the mass ratio of the graphite particles to the nickel particles is (3-5):1.
[0021] In some embodiments of the present invention, the mass of the sulfonated graphene nanosheets is 3%-8% of the total mass of the nickel particles and graphite particles.
[0022] In some preferred embodiments of the present invention, the mass of the sulfonated graphene nanosheets is 4%-6% of the total mass of the nickel particles and graphite particles.
[0023] In some embodiments of the present invention, the mass ratio of the aniline monomer, dodecylbenzenesulfonic acid and sulfonated graphene nanosheets is 1: (2.5-4.5): (7-11).
[0024] In some preferred embodiments of the present invention, the mass ratio of the aniline monomer, dodecylbenzenesulfonic acid and sulfonated graphene nanosheets is 1: (3-4): (8-10).
[0025] The second aspect of the present invention provides a method for preparing the core-shell structured composite conductive material described in the first aspect of the present invention, comprising the following steps: A dispersion containing sulfonated graphene nanosheets and an emulsion containing aniline monomer and dodecylbenzenesulfonic acid are mixed to form a mixture. Nickel particles and graphite particles are added to the mixture to form a mixed system; The mixture is subjected to in-situ polymerization under oxidizing conditions to obtain the core-shell structured composite conductive material.
[0026] In some embodiments of the present invention, the concentration of sulfonated graphene nanosheets in the dispersion is 1-3 mg / mL.
[0027] In some embodiments of the present invention, the solvent of the dispersion is water.
[0028] In some embodiments of the present invention, the solvent of the emulsion is water.
[0029] In some embodiments of the present invention, the in-situ polymerization reaction includes the addition of an oxidant, wherein the mass ratio of the oxidant to the aniline monomer is 1:(2-5).
[0030] In some preferred embodiments of the present invention, the mass ratio of the oxidant to the aniline monomer is 1:(2-3).
[0031] In some embodiments of the present invention, the oxidant is selected from ammonium persulfate (APS), potassium persulfate (KPS), or a combination thereof.
[0032] In some embodiments of the present invention, the in-situ polymerization reaction is carried out at a temperature of 0-5°C for 2-4 hours.
[0033] In some embodiments of the present invention, the in-situ polymerization reaction is carried out under ice-water bath conditions.
[0034] In some embodiments of the present invention, after the in-situ polymerization reaction is completed, the process further includes solid-liquid separation to collect the solid phase, washing, drying, crushing, and sieving.
[0035] In some embodiments of the present invention, the washing reagent includes water and ethanol.
[0036] In some embodiments of the present invention, the drying temperature is 50-70°C and the time is 40-60 hours.
[0037] In some preferred embodiments of the present invention, the drying temperature is 55-65°C and the time is 45-55 hours.
[0038] The basic principles of this invention are explained as follows: The core-shell structured composite conductive material provided by this invention uses graphite particles and nickel particles as the core, and utilizes dodecylbenzene sulfonic acid (DBSA) as an emulsifier and dopant to construct a stable emulsion. Sulfated graphene (SGO), graphite particles, and nickel particles are introduced into the emulsion system. Under low-temperature conditions (0-5℃), aniline monomers are oxidized and polymerized in situ on the surface of the core material through oxidation, allowing sulfonated graphene nanosheets to be uniformly embedded in the polyaniline matrix, forming a core-shell structured composite conductive material. The sulfonated graphene retains a relatively complete conjugated structure of graphene and has good conductivity. It is far superior to graphene oxide; simultaneously, the sulfonic acid group (-SO3H) can serve as a p-type doping site, forming a dual sulfonic acid doping system with dodecylbenzenesulfonic acid, further enhancing the conductivity and stability of polyaniline; the sulfonic acid group also endows sulfonated graphene with good water dispersibility and surface charge, and is fully compatible with existing polyaniline synthesis processes; sulfonated graphene nanosheets are embedded in the polyaniline matrix, and electrons can be rapidly conducted through the sulfonated graphene sheets, breaking through the limitation of electron-dependent inter-chain jumping conduction in the pure polyaniline shell; the density of the composite shell is approximately 1.3 g / cm³. 3 After being coated on the surface of high-density nickel powder, it can effectively reduce the equivalent density of the particles and slow down the settling speed; the sulfonic acid groups on the surface of sulfonated graphene give the particle surface a high zeta potential, generating electrostatic repulsion between particles and preventing agglomeration.
[0039] A third aspect of the present invention provides a coating comprising a base paint and a curing agent, wherein the base paint comprises the core-shell structured composite conductive material described in the first aspect of the present invention.
[0040] In some embodiments of the present invention, the mass ratio of the main paint to the curing agent is (1-3):1.
[0041] In some preferred embodiments of the present invention, the mass ratio of the main paint to the curing agent is (1.5-2.5):1.
[0042] In some embodiments of the present invention, the curing agent comprises a modified polyamide resin.
[0043] In some embodiments of the present invention, the main paint comprises, by weight, the following components: 80-120 parts of bisphenol A type epoxy resin, 30-45 parts of core-shell structured composite conductive material, 0.5-2 parts of sulfonated graphene, 1.5-4.5 parts of thixotropic agent, 25-40 parts of solvent, 1-3 parts of silane coupling agent, 0.3-0.8 parts of defoamer, and 0.3-0.8 parts of leveling agent.
[0044] In some preferred embodiments of the present invention, the main paint comprises, by weight, the following components: 90-110 parts of bisphenol A type epoxy resin, 35-45 parts of core-shell structured composite conductive material, 0.5-1.5 parts of sulfonated graphene, 2-4 parts of thixotropic agent, 25-30 parts of solvent, 1.5-2.5 parts of silane coupling agent, 0.4-0.6 parts of defoamer, and 0.4-0.6 parts of leveling agent.
[0045] In some embodiments of the present invention, the epoxy equivalent of the bisphenol A type epoxy resin is 180-210 g / eq.
[0046] In some embodiments of the present invention, the thixotropic agent is selected from fumed silica, organobentonite, or a combination thereof.
[0047] In some preferred embodiments of the present invention, the thixotropic agent is a mixture of fumed silica and organobentonite in a mass ratio of 1:(1.5-2.5) by weight.
[0048] In some embodiments of the present invention, the solvent is selected from xylene, n-butanol, or a combination thereof.
[0049] In some preferred embodiments of the present invention, the solvent is a mixture of xylene and n-butanol in a mass ratio of (6-8):1.
[0050] In some embodiments of the present invention, the silane coupling agent is selected from γ-glycidoxypropyltrimethoxysilane (KH-560), 3-aminopropyltriethoxysilane (KH-550), or a combination thereof.
[0051] In some embodiments of the present invention, the coating is prepared by a method comprising the following steps: The core-shell structured composite conductive material, silane coupling agent and solvent are mixed and ground to a fineness of ≤30μm; Bisphenol A type epoxy resin, sulfonated graphene nanosheets, thixotropic agent, defoamer and leveling agent are added in sequence to obtain the main paint; The main paint is mixed with a curing agent to obtain the coating.
[0052] In some embodiments of the present invention, the mixing process is supplemented by high-speed dispersion, wherein the high-speed dispersion speed is 1500-2500 rpm.
[0053] In some preferred embodiments of the present invention, the high-speed dispersion rotation speed is 800-1200 rpm.
[0054] In some preferred embodiments of the present invention, the high-speed dispersion rotation speed is 400-600 rpm.
[0055] In some embodiments of the present invention, the 30-day settling rate of the coating is ≤5%.
[0056] The coating provided by this invention, in addition to the core-shell structured composite conductive material, also introduces free sulfonated graphene into the formulation. Utilizing its high aspect ratio sheet structure (aspect ratio greater than 1000), a three-dimensional overlapping network is constructed in the coating. On the one hand, it serves as a conductive bridge between core-shell particles to improve the continuity of the conductive network. On the other hand, the network structure supports the particles and inhibits sedimentation. Combined with a thixotropic agent system composed of fumed silica and organic bentonite, the coating has high viscosity when standing to prevent sedimentation, and its viscosity decreases during shearing and stirring to facilitate construction.
[0057] A fourth aspect of the present invention provides a coating formed by curing the coating described in the third aspect of the present invention.
[0058] In some embodiments of the present invention, the thickness of the coating is 80-150 μm.
[0059] In some embodiments of the present invention, the volume resistivity of the coating is ≤1×10⁻⁶. -3 Ω·cm.
[0060] The fifth aspect of the present invention provides the application of the coating described in the fourth aspect of the present invention in the surface protective treatment of steel components of grounding grids.
[0061] Compared with the prior art, the beneficial effects of the present invention are: The core-shell structured composite conductive material provided by this invention allows sulfonated graphene to be uniformly embedded in a polyaniline matrix to form an integrated composite shell, effectively solving the key problems of insufficient conductivity and easy agglomeration and sedimentation of traditional conductive fillers. The core-shell structured composite conductive material provided by this invention significantly improves the material's conductivity through the highly conductive framework of sulfonated graphene and the doping effect of sulfonic acid groups, combined with the synergistic doping effect of dodecylbenzenesulfonic acid. Electrons can be rapidly conducted through the sulfonated graphene sheets, overcoming the conductivity limitations of pure polyaniline. At the same time, the composite shell reduces the equivalent density of particles, and the high zeta potential of the sulfonic acid groups on the particle surface generates electrostatic repulsion to inhibit agglomeration, greatly improving the dispersion stability of the filler and laying a core foundation for the stable application of subsequent coating systems. The coating provided by this invention possesses excellent electrical conductivity, storage stability, and long-term corrosion resistance. Free sulfonated graphene in the coating constructs a three-dimensional interconnected network, serving as conductive bridges between particles to complete the continuous conductive network, resulting in a coating volume resistivity ≤1×10⁻⁶. -3 With a strength of Ω·cm, it can stably discharge large currents and physically support the filler to inhibit settlement; combined with a thixotropic system of fumed silica and organic bentonite, it achieves the characteristics of static anti-settlement and easy application, with a 30-day settlement rate of ≤5%; The coating provided by this invention is dense and strong. Polyaniline and sulfonated graphene work together to form a passivation barrier, blocking the penetration of corrosive media. The conductivity remains stable after long-term immersion in a high-salt environment, effectively extending the service life of the grounding grid and meeting the protection requirements of the complex service environment of power grounding grids. Attached Figure Description
[0062] Figure 1 This is a TEM image of the core-shell structured composite conductive material in Example 1; Figure 2 This is a SEM image of the coating formed by the curing of the paint in Application Example 1; Figure 3 A comparison diagram of the settling stability of the coatings in Application Example 1 and Comparative Example 1; Figure 4 This is a comparison chart showing the corrosion resistance and electrical conductivity stability of the coatings formed by the paints in Application Example 1 and Comparative Example 1. Detailed Implementation
[0063] The present invention will be further described in detail below with reference to specific accompanying drawings and embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the experimental or testing methods are conventional methods in the art.
[0064] Unless otherwise specified, "parts" in Examples 1, Comparative Examples, Application Examples and Application Comparative Examples refer to "parts by mass".
[0065] Example 1 This embodiment prepares a core-shell structured composite conductive material, and the steps are as follows: 1. Preparation of sulfonated graphene (SGO): 1) Preparation of graphene oxide using the modified Hummers method: Weigh 2.0 g of natural flake graphite (325 mesh) and 1.0 g of sodium nitrate into a three-necked flask containing 46 mL of concentrated sulfuric acid (98 wt%), and stir for 30 min in an ice-water bath; slowly add 6.0 g of potassium permanganate, controlling the temperature not to exceed 20 °C, and stir for 2 h. Transfer the reaction system to a 35 °C water bath and continue stirring for 1 h. Then slowly add 92 mL of deionized water, raise the temperature to 98 °C and hold for 15 min; add 280 mL of hot deionized water and 10 mL of 30 wt% hydrogen peroxide to terminate the reaction, filter while hot, and wash repeatedly with 5 wt% hydrochloric acid solution and deionized water until the filtrate is neutral. Disperse the filter cake in deionized water, ultrasonically peel it for 2 h, centrifuge to remove the unpeeled graphite, and freeze-dry to obtain graphene oxide powder; 2) Grafting sulfonic acid groups onto the surface of graphene oxide using a diazotization reaction: 1.0 g of graphene oxide was ultrasonically dispersed in 500 mL of deionized water to form a uniform brownish-yellow dispersion. Separately, 3.0 g of p-aminobenzenesulfonic acid was dissolved in 50 mL of deionized water (with the addition of an appropriate amount of sodium hydroxide to aid dissolution). After cooling to 0-5℃, 20 mL of an aqueous solution containing 1.2 g of sodium nitrite was slowly added dropwise, maintaining the temperature at 0-5℃ during the addition. After the addition was complete, stirring was continued for 30 min to form a diazonium salt solution. The diazonium salt solution was slowly added dropwise to the graphene oxide dispersion, and the reaction was stirred in an ice-water bath for 4 h. After the reaction was complete, the product was transferred to a dialysis bag, dialyzed with deionized water for 3 days, and freeze-dried to obtain black sulfonated graphene powder.
[0066] 2. Preparation of core-shell structured composite conductive materials: S1. Raw material pretreatment: Weigh 16.0g of graphite powder (particle size 3-8μm) and place it in a beaker. Add 200mL of anhydrous ethanol and ultrasonically disperse it for 45min at 250W. After centrifugation, dry it in a vacuum drying oven at 60℃ for 12h for later use. Weigh 4.0g of nickel powder (particle size 1-3μm) and soak it in dilute hydrochloric acid (5wt%) for 5min to remove the surface oxide layer. Wash it with deionized water until neutral and then ultrasonically disperse and vacuum dry it using the same method for later use. S2. Weigh 1.0g of sulfonated graphene powder, add it to 500mL of deionized water, and ultrasonically disperse it for 45min at a power of 500W to obtain a dispersion with a concentration of 2mg / mL. S3. Add 400 mL of deionized water to a 1000 mL three-necked flask, then add 9.3 g of aniline monomer (freshly distilled) and 32.6 g of dodecylbenzenesulfonic acid in sequence. Stir mechanically at room temperature for 1 h to form a uniform and stable milky white emulsion. S4. Add the dispersion prepared in step S2 to the emulsion prepared in step S3, and continue stirring for 30 minutes to mix it evenly and form a mixed system. S5. Add the pretreated graphite powder and nickel powder to the mixing system, and ultrasonically treat for 30 minutes under a power of 300W, while mechanically stirring to ensure that the graphite powder and nickel powder are evenly dispersed. Adjust the pH of the system to 1.5±0.2 with dilute hydrochloric acid. S6. Place the system from step S5 in an ice-water bath and control the temperature within the range of 0-5℃. Under continuous mechanical stirring (300 rpm), slowly add 100 mL of an aqueous solution containing 27.4 g of ammonium persulfate to the reaction system dropwise over 1 hour using a constant flow pump. During the dropwise addition, observe that the color of the system gradually changes from gray to dark green. After the dropwise addition is complete, continue stirring the reaction in the ice-water bath for 3 hours. S7. After the reaction is complete, the product is centrifuged at 8000 rpm for 15 min, the supernatant is discarded, and the product is washed three times each with deionized water and anhydrous ethanol. The washed product is then dried in a vacuum drying oven at 60℃ for 48 h and ground through a 200-mesh sieve to obtain a dark green core-shell structured composite conductive material.
[0067] Figure 1 This is a TEM image of the core-shell structured composite conductive material in Example 1. Figure 1 It can be seen that the composite conductive material prepared in Example 1 exhibits a typical core-shell structure morphology, with a dark graphite / nickel powder core being uniformly and continuously coated with a composite shell.
[0068] Comparative Example 1 This comparative example prepares a composite conductive material, and the steps are as follows: S1. Raw material pretreatment: Weigh 16.0g of graphite powder (particle size 3-8μm) and place it in a beaker. Add 200mL of anhydrous ethanol and ultrasonically disperse it for 45min at 250W. After centrifugation, dry it in a vacuum drying oven at 60℃ for 12h for later use. Weigh 4.0g of nickel powder (particle size 1-3μm) and soak it in dilute hydrochloric acid (5wt%) for 5min to remove the surface oxide layer. Wash it with deionized water until neutral and then ultrasonically disperse and vacuum dry it using the same method for later use. S2. Add 400 mL of deionized water to a 1000 mL three-necked flask, then add 9.3 g of aniline monomer (freshly distilled) and 32.6 g of dodecylbenzenesulfonic acid in sequence. Stir mechanically at room temperature for 1 h to form a uniform and stable milky white emulsion. S3. Add 500 mL of deionized water to the emulsion prepared in step S2, and continue stirring for 30 min to mix it evenly and form a mixed system. S4. Add the pretreated graphite powder and nickel powder to the mixing system, and ultrasonically treat for 30 minutes under a power of 300W, while mechanically stirring to ensure that the graphite powder and nickel powder are evenly dispersed. Adjust the pH of the system to 1.5±0.2 with dilute hydrochloric acid. S5. Place the system from step S4 in an ice-water bath and control the temperature within the range of 0-5℃. Under continuous mechanical stirring (300 rpm), slowly add 100 mL of an aqueous solution containing 27.4 g of ammonium persulfate to the reaction system dropwise over 1 hour using a constant flow pump. During the dropwise addition, observe that the color of the system gradually changes from gray to dark green. After the dropwise addition is complete, continue stirring the reaction in the ice-water bath for 3 hours. S6. After the reaction is complete, the product is centrifuged at 8000 rpm for 15 min, the supernatant is discarded, and the product is washed three times each with deionized water and anhydrous ethanol. The washed product is then dried in a vacuum drying oven at 60℃ for 48 h and ground through a 200-mesh sieve to obtain the composite conductive material.
[0069] Application Example 1 The core-shell structured composite conductive material prepared in Example 1 was used to prepare coatings. The components and contents of the coatings are shown in Table 1 below: Table 1. Components and content of the coating in Application Example 1
[0070] The preparation steps of the coating are as follows: According to the formula in Table 1, the core-shell structured composite conductive material was mixed with silane coupling agent and part of xylene, and dispersed in a high-speed shear disperser at 2000 rpm for 30 min. Then, it was ground to a fineness of ≤30 μm by a sand mill. The ground slurry was transferred to a mixing tank, bisphenol A type epoxy resin was added, and it was stirred at 1000 rpm for 30 min. Then, xylene dispersion of sulfonated graphene (solid content 5 wt%) was added, and it was stirred at low speed at 500 rpm for 15 min (to protect the sulfonated graphene sheet structure). Fumed silica and organobentonite were added, and it was dispersed at 1000 rpm for 20 min. Finally, defoamer and leveling agent were added, and it was stirred at low speed until uniform. Solvent was added to adjust the viscosity, and the mixture was filtered through a 200-mesh filter to obtain the main paint. Modified polyamide resin (Green Union (Ji) Chemical Technology Co., Ltd., TV8140) was used as a curing agent. The main paint and curing agent were mixed at a mass ratio of 2:1, stirred evenly, and allowed to stand for 15 minutes to mature, thus obtaining the coating.
[0071] Application Comparative Example 1 The composite conductive material prepared in Comparative Example 1 was used to prepare coatings. The components and contents of the coatings are shown in Table 2 below: Table 2. Components and content of the coatings used in Comparative Example 1
[0072] The preparation steps of the coating are as follows: According to the formula in Table 2, the composite conductive material is mixed with silane coupling agent and part of xylene, and dispersed in a high-speed shear disperser at 2000 rpm for 30 min. Then, it is ground to a fineness of ≤30 μm by a sand mill. The ground slurry is transferred to a mixing tank, bisphenol A epoxy resin is added, and it is stirred at 1000 rpm for 30 min. Fumed silica and organobentonite are added, and it is dispersed at 1000 rpm for 20 min. Finally, defoamer and leveling agent are added, and it is stirred at low speed until uniform. Solvent is added to adjust the viscosity, and the mixture is filtered through a 200-mesh filter to obtain the main paint. Modified polyamide resin (Green Union (Ji) Chemical Technology Co., Ltd., TV8140) was used as a curing agent. The main paint and curing agent were mixed at a mass ratio of 2:1, stirred evenly, and allowed to stand for 15 minutes to mature, thus obtaining the coating.
[0073] Performance testing The performance of the coatings prepared in Use Case 1 and Application Comparison Example 1 was tested, as follows: 1. The coating prepared in Application Example 1 was applied to a sandblasted Q235 steel plate (100mm×100mm×3mm) using a scraping method. The dry film thickness was 100±10μm. After curing at room temperature for 7 days, the following tests were performed: 1) Conductivity test: The high-precision four-probe method was used for testing. The entire measurement process was carried out under constant temperature and humidity (25℃, 50%RH). Five different positions were selected at the center and around the sample for measurement. At each position, a known stable current (10mA) was applied through the outer probe, and the voltage difference between the inner probes was accurately measured. 2) High-current impulse test: To realistically simulate the destructive effect of lightning, a generator capable of producing a standard 8 / 20μs lightning impulse waveform was selected for testing. The test was conducted in a shielded laboratory with a temperature of 25±2℃ and a relative humidity of 50%±5%. The current impulse was applied to the diagonal ends of the sample, forcing the current to flow through the entire coating surface. The peak impulse current was set to 20kA, and multiple impulses were performed. The resistance value of the coating was measured before and after the impulse, and its rate of change was calculated. The rate of change is calculated as: (coating surface resistance after impulse - coating surface resistance before impulse) / coating surface resistance before impulse × 100%. 3) Weather resistance test: The sample was placed in a high and low temperature alternating damp heat test chamber and subjected to temperature control cycle test. The cycle conditions were set as follows: cooling from 25℃ to -10℃ and holding for 1 hour, then heating to 85℃ and holding for 1 hour. This is one cycle. A total of 50 cycles were performed. After completing 50 cycles, the sample was allowed to stand and recover for 2 hours under standard test conditions, and its volume resistivity was measured again using the same method.
[0074] Figure 2 The image shows a SEM image of the coating formed by the curing of the paint in Example 1. Figure 2 As can be seen, the cured coating surface exhibits a smooth and dense microstructure, with conductive particles evenly distributed on the coating surface. The initial average volume resistivity of the coating was measured to be 8.5 × 10⁻⁶. -4 The surface resistivity of the coating, measured using the two-electrode method, was 0.18 Ω·cm. The surface morphology of the coating showed no significant change after high-current impact. After five impacts, the surface resistivity increased from 0.18 Ω to 0.19 Ω, with a cumulative change rate of 5.6% (<10%). The average volume resistivity after temperature-controlled cycling was 9.0 × 10⁻⁶.-4 The volume resistivity change rate is less than 10%, indicating that the internal conductive network of the coating remains highly stable after repeated and drastic temperature changes.
[0075] 2. Conduct anti-settling performance tests on the coatings corresponding to Case 1 and Application Comparison Example 1: Take 500 mL of the coating from Application Example 1 and Application Comparative Example 1 respectively and place them in a wide-mouthed cylindrical container (inner diameter 80 mm, height approximately 150 mm). Seal the container opening with plastic wrap to prevent solvent evaporation. Place the container vertically and stand. On the 7th, 14th, 21st and 30th days of standing, carefully insert a scraper along the inner wall of the container and take approximately 10 g of sample from the top (within 10 mm below the liquid surface, i.e., the upper 1 / 3 layer). Place the sample in a forced-air drying oven and bake for 2 hours to fully remove the solvent. After removing the sample, place it in a desiccator to cool to room temperature and weigh the solid residue. Calculate the solid content using the following formula: Solid content (%) = Mass of solid after baking (g) / Total mass of sample (g) × 100%.
[0076] Figure 3 Table 3 shows the settling stability comparison chart of the coatings in Application Example 1 and Comparative Example 1, and the test results of the settling stability of the coatings in Application Example 1 and Comparative Example 1 are presented in Table 3. Figure 3 As shown in Table 3, the solid content of the coating in Application Example 1 remained relatively stable during the 30-day standing period. By the 30th day, the solid content had decreased by 3.08%, indicating that the conductive filler was evenly distributed throughout the storage period and no serious sedimentation occurred. In contrast, the solid content of the coating in Application Comparative Example 1 decreased by 7.29% on the 7th day and by 16.53% on the 30th day under the same test conditions. This indicates that the viscosity was insufficient to effectively suppress the sedimentation of high-density particles under standing conditions, proving that the coating provided by this invention has excellent anti-settling ability.
[0077] Table 3. Settling stability test results of coatings in Application Example 1 and Comparative Application Example 1
[0078] 3. Conduct corrosion resistance and electrical conductivity stability tests on the coatings formed by the paints in corresponding use case 1 and application comparison example 1: The coatings prepared in Application Example 1 and Comparative Example 1 were applied to sandblasted Q235 steel plates (100mm×100mm×3mm) using a scraping method, with a dry film thickness of 100±10μm. After curing at room temperature for 7 days, the following tests were performed: Both types of samples were completely immersed in a 3.5 wt% sodium chloride solution. The entire immersion process was carried out in a constant temperature environment of 25 ± 1℃. At different time points during the immersion process (days 0, 15, 30, 45, 60, 75, and 90), the samples were taken out, rinsed with deionized water, and dried. The volume resistivity of the coating was measured using the four-probe method. After the measurement was completed, the samples were put back into the solution for further immersion.
[0079] Figure 4 This is a comparison chart showing the corrosion resistance and electrical conductivity stability of the coatings formed by the paints in Application Example 1 and Comparative Example 1. Figure 4 It can be seen that the coatings formed by the paints in Application Example 1 and Comparative Example 1 both exhibit good anti-corrosion performance, and the change in volume resistivity remains at an extremely low level, indicating that both have relatively stable composite conductive networks. In comparison, the coating formed by the paint in Application Example 1 has an even lower resistivity, which remains ≤1.0×10⁻⁶ throughout the 90-day immersion period. -3 The Ω·cm indicates that it has superior conductivity, which is attributed to the fact that the polyaniline shell inhibits the corrosion of the metal substrate through a dual mechanism of passivation film formation and barrier effect; the composite shell structure is dense and has strong adhesion, which blocks the penetration of corrosive media.
[0080] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A core-shell structured composite conductive material, characterized in that, It includes a core containing nickel particles and graphite particles, and a shell covering the surface of the core, wherein the shell is a composite conductive layer formed by embedding sulfonated graphene nanosheets into a polyaniline matrix.
2. The core-shell structured composite conductive material according to claim 1, characterized in that, The nickel particles have a particle size of 1-5 μm; And / or, the graphite particles have a particle size of 1-10 μm; And / or, the diameter of the sulfonated graphene nanosheets is 5-15 μm; And / or, the particle size of the core-shell structured composite conductive material is less than or equal to 200 mesh.
3. The core-shell structured composite conductive material according to claim 1 or 2, characterized in that, The core-shell structured composite conductive material comprises the following raw materials: nickel particles, graphite particles, sulfonated graphene nanosheets, aniline monomer, and dodecylbenzenesulfonic acid.
4. The core-shell structured composite conductive material according to claim 3, characterized in that, The mass ratio of the graphite particles to the nickel particles is (3-9):1; And / or, the mass of the sulfonated graphene nanosheets is 3%-8% of the total mass of the nickel particles and graphite particles; And / or, the mass ratio of the aniline monomer, dodecylbenzenesulfonic acid and sulfonated graphene nanosheets is 1: (2.5-4.5): (7-11).
5. The method for preparing the core-shell structured composite conductive material according to any one of claims 1-4, characterized in that, Includes the following steps: A dispersion containing sulfonated graphene nanosheets and an emulsion containing aniline monomer and dodecylbenzenesulfonic acid are mixed to form a mixture. Nickel particles and graphite particles are added to the mixture to form a mixed system; The mixture is subjected to in-situ polymerization under oxidizing conditions to obtain the core-shell structured composite conductive material.
6. The preparation method according to claim 5, characterized in that, The in-situ polymerization reaction is carried out at a temperature of 0-5℃ for 2-4 hours.
7. A coating comprising a base paint and a hardener, characterized in that, The main paint includes the core-shell structured composite conductive material as described in any one of claims 1-4.
8. The coating according to claim 7, characterized in that, By weight, the main paint comprises the following components: 80-120 parts of bisphenol A type epoxy resin, 30-45 parts of core-shell structured composite conductive material, 0.5-2 parts of sulfonated graphene, 1.5-4.5 parts of thixotropic agent, 25-40 parts of solvent, 1-3 parts of silane coupling agent, 0.3-0.8 parts of defoamer, and 0.3-0.8 parts of leveling agent.
9. A coating, characterized in that, It is formed by curing the coating as described in claim 7 or 8.
10. The application of the coating as described in claim 7 or 8 in the surface protective treatment of steel components of grounding grids.